Restorative Justice Perkara Narkotika Menurut Perkapolri Nomor 8 Tahun 2021 - Aguk Nugroho (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
One of the efforts to resolve crimes that occur in people's lives is not only through law enforcement efforts, but through a restorative justice approach that is different from the conventional criminal justice system, where this approach emphasizes the direct participation of perpetrators, victims and the community in the process of resolving criminal cases. The aims of this study are (1) to find out the application of restorative justice in narcotics cases in Indonesia; (2) To find out the legal considerations of restorative justice in narcotics cases in Indonesia. Empirical normative research type. Normative legal research (applied law research) is research that uses normative legal case studies in the form of legal behavior products. This study uses a qualitative analysis method, which is in the form of an in-depth interpretation of legal materials as is usually the case with normative legal research. In carrying out the application of restorative justice in narcotics cases in Indonesia, it has been carried out well from a procedural point of view. Basically, criminal cases can be stopped at the stage of investigation and/or investigation based on restorative justice only on crimes that are not serious crimes. Legal considerations of restorative justice in narcotics cases in Indonesia, namely by balancing the interests of various parties (perpetrators, victims, society and the State); Non-compliance with the guidelines and basic principles that have been formulated on the basis of the principles of "human development, mutually, empathy, responsibility; respect and fairness”; The feelings of victims who feel they are experiencing "re-victimization" because they feel pressured; Attempts from the formal criminal justice system to take over the restorative justice movement.